Legal Formulation of Public-Private Partnership Designing a Solar Power Plant in Underdeveloped Areas - Nurfajriana, Syifa; Nugroho, Andriyanto Adhi (Unram Law Review, 2025)
Underdeveloped regions have high potential for Solar Power Plants (PLTS), as data from the Institute for Essential Services Reform (IESR) indicates. The main challenges in developing PLTS in these areas are related to financing and the supply of solar panel materials. Therefore, the implementation of Presidential Regulation No. 105 of 2021 concerning the National Strategy for Accelerating the Development of Underdeveloped Regions for 2020-2024 (Perpres 105/2021) is necessary, mainly through the establishment of silica industry manufacturing companies to support PLTS and financing schemes such as Public-Private Partnerships (PPP) in PLTS development. The research problem focuses on how regulatory implementation in PLTS development can advance underdeveloped regions and how formulating the PPP financing scheme can support PLTS infrastructure development in these areas. This study aims to examine regulations in PLTS development that contribute to the progress of the remote regions and analyse the formulation of PPP financing schemes to accelerate PLTS infrastructure in underdeveloped areas. This study employs normative legal research using statutory, conceptual, and comparative approaches. The findings indicate that establishing silica industry manufacturing companies to support PLTS is essential, with various stakeholders’ support, as Perpres 105/2021 stipulated. Additionally, a specific PPP regulation is required to govern PPP schemes in underdeveloped regions.